Interface between an Au(111) Surface and an Ionic Liquid: The Influence of Water on the Double‐Layer Capacitance. Issue 1 (31st October 2016) - Friedl, Jochen; Markovits, Iulius I. E.; Herpich, Max; Feng, Guang; Kornyshev, Alexei A.; Stimming, Ulrich
Abstract: The presence of water in room‐temperature ionic liquids (RTILs) can have a strong effect on their properties. In particular, water adsorption at electrodes can reduce the electrochemical potential window of the system. It is, thus, important to understand where water will be present depending on the electrode potential, the type of ionic liquid, and the electrode material. We investigate the influence of water on RTILs by measuring the potential‐dependent double‐layer capacitance of various water–RTIL mixtures. The resulting capacitance versus potential curves are reproduced employing mean‐field theory calculations. From the parameters used to obtain the best agreement between experimental and theoretical curves, some properties of the RTILs can be deducted, such as a stronger interaction of water with RTIL anions than cations and an agglomeration of water at potentials positive or negative of the potential of zero charge. Abstract : Water cap : The interface between an Au(111) electrode and an ionic liquid with varying water contents is investigated by using electrochemical impedance spectroscopy. The obtained double‐layer capacitance versus potential curves show that water adsorbs at the electrode and increases the capacitance. These curves can also be reproduced with mean‐field theory calculations.